2016
DOI: 10.1080/09640568.2016.1162138
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the socio-economic impacts of green/blue space, urban residential and road infrastructure projects in the Confluence (Lyon): a hedonic pricing simulation approach

Abstract: Urban green/blue spaces are put under pressure as urban areas grow, develop and evolve. It is increasingly recognized, however, that green/blue spaces provide important ecosystem services, stimulate higher real estate prices and prevent flooding problems. This paper aims to assess and compare the socio-economic impacts of potential green/blue space, urban residential and road infrastructure development scenarios in the Lyon Confluence project area (France), using the Sustainable Urbanizing Landscape Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 55 publications
1
17
0
3
Order By: Relevance
“…Therefore, HPM is more suitable for estimating the value inherent in a preference [28,29]. In fact, many studies have used HPM to estimate the value of the ecosystem services, including parks, inherent in housing prices [7,25,26,[32][33][34][35][36] HPM is the study of the relationship between the price of a commodity or house and its characteristics [28,29,37]. For example, people buy real estate, such as an apartment or house, because they expect to gain utility and enjoyment from the house.…”
Section: Hedonic Price Methods (Hpm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, HPM is more suitable for estimating the value inherent in a preference [28,29]. In fact, many studies have used HPM to estimate the value of the ecosystem services, including parks, inherent in housing prices [7,25,26,[32][33][34][35][36] HPM is the study of the relationship between the price of a commodity or house and its characteristics [28,29,37]. For example, people buy real estate, such as an apartment or house, because they expect to gain utility and enjoyment from the house.…”
Section: Hedonic Price Methods (Hpm)mentioning
confidence: 99%
“…Escobedo et al [33] used two categories of variables, house characteristics and urban forest attributes, to estimate the effect of forest structures on property value. Roebeling et al [7] and Payton et al [34] also used three qualities of urban parks to value the benefits provided by city parks. Ko et al [25] and Kim et al [35] estimated the value of green space with three variable categories, which include attributes such as property area, age, size of apartment complex, school district, and accessibility to public transport and parks.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the socieconomic impacts of GI using a hedonic pricing simulation approach for Confluence (Lyon, France) revealed four major trends associated with GI adoption, namely, "1) cities become more compact 2) population densities increase 3) real estate values rise and 4) demographic distribution patterns change." Impacts were dependent on the quality and size of the GI, the social classes attracted to GI and the location relative to urban areas (Roebeling et al, 2017). Evaluating the potential econonomic co-benefits of GI installations in Baltimore (Maryland, USA) found that houses located adjacent to stormwater retention basins were 13% to 14% less than the average home implying a cost as opposed to a benefit (Irwin et al, 2017).…”
Section: Planning and Ecosystem Service Evaluationmentioning
confidence: 99%
“…Bin et al [33] used a spatial autoregressive model to investigate the effects of flood risk on property values; in other cases, GIS has been used for deriving the location characteristics of the buildings [7,34]. A particular use of GIS in connection with hedonic pricing methods was made by Roebeling et al [35], who implemented a hedonic pricing simulation model into a GIS raster model for the ex-ante assessment of changes in real estate prices associated with development scenarios for green/blue spaces, and urban residential and road infrastructure developments in the city of Lyon.…”
Section: The Use Of Hedonic Approach For the Assessment Or Urban Qualitymentioning
confidence: 99%